Synthesis of a DNA Promoter Segment Containing All Four Epigenetic Nucleosides: 5‐Methyl‐, 5‐Hydroxymethyl‐, 5‐Formyl‐, and 5‐Carboxy‐2′‐Deoxycytidine1. Issue 1 (26th November 2013) - Schröder, Arne S.; Steinbacher, Jessica; Steigenberger, Barbara; Gnerlich, Felix A.; Schiesser, Stefan; Pfaffeneder, Toni; Carell, Thomas
Abstract A 5‐formyl‐2′‐deoxycytidine (fdC) phosphoramidite building block that enables the synthesis of fdC‐containing DNA with excellent purity and yield has been developed. In combination with phosphoramidites for 5‐methyl‐dC, 5‐hydroxymethyl‐dC, and carboxy‐dC, it was possible to prepare a segment of the OCT‐4 promoter that contains all four epigenetic bases. Because of the enormous interest in these new epigenetic bases, the ability to insert all four of them into DNA should be of great value for the scientific community.